2017
DOI: 10.3329/cmoshmcj.v16i1.34986
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the Left Coronary Artery

Abstract: Background : There is a large spectrum of variations in the disposition of coronary arteries. Many of these variations are 'normal' and not considered as 'anomalous'1 . These variations mainly occur in the Left Coronary Artery (LCA) 2 . While some of these are benign and have no clinical consequences, other variants can cause important clinical manifestations including sudden death of the individual 3 . Lack of knowledge of such variations can pose difficulties in percuteneous coronary arteriography, coronary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
(5 reference statements)
0
0
0
Order By: Relevance
“…For instance, LMCA lengths less than 5 mm are considered to be short LMCA trunks and are associated with a high risk of injury when angiography is performed. Some cadaveric studies reported the mean length of LMCA to be 9.2±0.31 mm [ 4 ] and ranging from 5-20 mm [ 5 ]. Most CTA studies showed a relatively longer LMCA with a mean LMCA length of 9.9±4.15 mm [ 6 ], 10.0±4.5 mm [ 7 ], and 10.5±4 mm [ 8 ] (Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, LMCA lengths less than 5 mm are considered to be short LMCA trunks and are associated with a high risk of injury when angiography is performed. Some cadaveric studies reported the mean length of LMCA to be 9.2±0.31 mm [ 4 ] and ranging from 5-20 mm [ 5 ]. Most CTA studies showed a relatively longer LMCA with a mean LMCA length of 9.9±4.15 mm [ 6 ], 10.0±4.5 mm [ 7 ], and 10.5±4 mm [ 8 ] (Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%